Dr Jekyll and Mr Hyde: Feedback and Welfare When Hedgers Can Acquire Information - Olivier, Jacques (Journal of Financial and Quantitative Analysis, 2026)
Abstract I ask whether hedgers who speculate should be regulated differently from other speculators in a model where information acquisition is endogenous, and information has real effects. Hedging benefits and feedback effects generate strategic complementarities between market-maker, firm manager, and trader, which causes multiple equilibria. Gains from trade are lower when hedgers acquire information, while speculators may produce less information than socially desirable. A “Volcker rule” separating hedging and speculative activities may help select the higher welfare equilibrium. When too little information is produced, contracts whereby a firm subsidizes losses of designated market-makers (DMM) to make prices more informative increase welfare.